(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2019)
After examining the peculiar aspects that characterize the legal regulation of the digital society, the contribution deals with the pervasive impact of technologies on human rights. In the light of the possibilities allowed by technological evolution, the so-called ICT freedom today assumes a broad meaning as the right to the development of one’s own digital existence, which allows and conditions the exercise of individual and social rights. This meta-right, an umbrella under which to give hospitality to the rights invested by technological development, requires protection based on the centrality of the person, on the quality of the data, on the technology and on the responsibility of the subjects, also envisaging new forms of collective protection. The protection of the right to digital existence can find an appropriate landing in an Internet Bill of Rights of supranational level, suitable to dictate common rules and to balance the interests involved.